Experimental Simulation of a Tennis Ball using Wind Tunnel - Souza, Cesar Almiro de (2023)
In this study, tennis balls were analyzed experimentally through the use of a wind tunnel with speed ranging from 1m/s to 14 m/s, which is a variation in the Reynolds number (10,000 < Re < 60,000). In this context, aerodynamic aspects of the balls were evaluated, including the position of the seam and the degree fuzz, i.e., with and without fuzz. It was possible to analyze the effect of drag on the diameter, in the investigation of the relationship between the drag coefficient (CD) and the Reynolds number (Re) for new and used balls. Graphics were generated using the Reynolds number and the Drag Coefficient in order to assess the (non) dependency of these parameters. In the measurements performed, the static balls inside the wind tunnel were considered, i.e., without rotation. Therefore, no discussions about the Magnus force are presented. The results obtained,  ? 3 to  ? 0.60, were consistent for the range of the Reynolds number investigated. High values are expected for the drag coefficient, to the range of Reynolds number examined. The position of the seam, according to the related literatures, is negligible to high values of Reynolds, i.e., Re >50,000. On the other hand, for low values of Reynolds number, it can represent a difference of up to about 9% for the CD. The balls without fluff showed the strongest influence of the position of the seam, which characterizes the influence of this parameter. The effect of fuzz seemed to be responsible for about 10% of the total drag for low values of the Reynolds number. The diameter variation was analyzed alone.